Study of particle interactions in a physical mixture of Mg stearate and methylorange - Breznik, Matej (Acta chimica slovenica, 2002)
It is of great interest to pharmaceutical technologists to be able to predict interactions between particles in mixtures in order to predict their behaviourduring technological processes and to control the pharmacokinetic andpharmacodynamic properties of the resulting dosage forms. In our study we used Mg stearate and methyl orange as model compounds to study the mixing behaviour. As expected, the mixture prepared with mortar and pestle in mass proportion 1Č1 was slightly coloured since Mg stearate particles (white) are covering the methyl orange. Our results show that Mg stearate has a lower surface free energy than methyl orange so, theoretically, particles of Mg stearate are expected to spread over the methyl orange particles. This was confirmed by calculation of spreading coefficients that gave positive spreading coefficients of Mg stearate over methyl orange. FT IR measurements for physical mixtures of Mg stearate and methyl orange in different proportions substantiate the spreading coefficient calculation. The results suggest that Mg stearate has a higher covering capacity at lower weight ratiosin mixtures with methyl orange.
Keywords: fizikalne lastnosti; magnezijev stearat; metil oranž; praški